EFFICIENCY UPGRADING OF VIBRATION TREATMENT THROUGH COMPUTER MODELLING - Evgenia M. Tamarkina (Advanced Engineering Research)
The results of the theoretical and field research and of the computer simulation of the vibration treatment are described. The metal removal parameters are defined. They make the quantitative prognosis of the treatment intensity in the vibro-finishing machines with different designs of work chambers possible. Some recommendations on their effective use in the performance of the specific tasks on the finishing machining are elaborated.